En performers død.: Funus Imaginarium som genfortryllelse af teatrale former i 2010 - Kuhlmann, Annelis (Peripeti, 2021)
The grave as a place of being for the identity and the national citizen in Das Beckwerk’s political performance Funus Imaginarium (2010) disposes its focus like a mise en abyme construction on the consequence of the hunger artist’s theatricalised concept of authorship, which is expressed as the death of a performer. The mimed ritual of the performance expands the notion of the relationship between participant and spectator into a dance macabre of critical and tragic-comical character. Through Funus Imaginarium the notion of mimesis has re-enchanted the performance in a new political frame with reference to Sofocle’s Antigone and the Roman funeral ritual ceremony.